Filtration Method with Three Media Combinations to Improve Rainwater Quality as A Drinking Water - Qori Nur Annisa; Prayudhy Yushananta; Bambang Murwanto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The high rate of population growth and industrialization impact increasing the need for clean water. Meanwhile, the quantity and quality of water are decreasing due to the exploitation of groundwater and industrial and domestic pollution. The utilization of rainwater is an alternative to sustainable water resources, but pollutants greatly influence its quality in the air. This study aims to improve the quality of rainwater as a source of drinking water by using the filtration method. The study used a completely randomized design with two replications. Three media were used (silica, zeolite, and activated carbon), and three thickness levels for each medium. Raw water is rainwater collected from the roofs of people's houses in industrial areas located by the sea, with the characteristics of dense population and heavy traffic. The water quality parameters observed were hardness, nitrite, nitrate, and sulfate. Water quality measurements were carried out before and after the experiment. The research has significantly proven that the combination of three media (silica, zeolite, and activated carbon) can improve the quality of rainwater on the parameters of hardness, nitrite, nitrate, and sulfate. The combination of the three media can reduce the value of hardness (37.9%), nitrite (73.18%), nitrate (61.32%), and sulfate (54.65%). The combination of thickness that is effective in reducing the values of the four parameters is 20 cm (silica), 40 cm (zeolite), and 40 cm (activated carbon). Overall, the parameters are in accordance with regulations. The filtration method with a combination of silica, zeolite, and activated carbon media effectively improve the chemical quality of rainwater so that it is suitable for consumption. However, the disinfection process needs to be carried out to eliminate microorganisms. Further research is needed to determine the saturation level of the filter media. Abstrak: Tingginya laju pertumbuhan penduduk dan industrialisasi berdampak pada meningkatnya kebutuhan akan air bersih. Sementara itu, kuantitas dan kualitas air semakin menurun akibat eksploitasi air tanah dan pencemaran industri dan domestik. Pemanfaatan air hujan merupakan salah satu alternatif sumber daya air yang berkelanjutan, namun kualitasnya sangat dipengaruhi polutan di udara. Penelitian ini bertujuan untuk meningkatkan kualitas air hujan sebagai sumber air minum dengan menggunakan metode filtrasi. Penelitian menggunakan rancangan acak lengkap faktorial dengan dua ulangan. Tiga media yang digunakan (silika, zeolit, dan karbon aktif), dan tiga tingkat ketebalan untuk setiap media. Air baku adalah air hujan yang ditampung dari atap rumah-rumah penduduk di kawasan industri yang terletak di tepi laut, dengan karakteristik padat penduduk dan padat lalu lintas. Parameter kualitas air yang diamati adalah kesadahan, nitrit, nitrat, dan sulfat. Pengukuran kualitas air dilakukan sebelum dan sesudah percobaan. Penelitian telah membuktikan bahwa kombinasi tiga media (silika, zeolit, dan karbon aktif) dapat meningkatkan kualitas air hujan pada parameter kesadahan, nitrit, nitrat, dan sulfat. Kombinasi ketiga media tersebut dapat menurunkan nilai kesadahan (37,9%), nitrit (73,18%), nitrat (61,32%), dan sulfat (54,65%). Kombinasi ketebalan yang efektif menurunkan nilai keempat parameter tersebut adalah 20 cm (silika), 40 cm (zeolit), dan 40 cm (karbon aktif). Secara keseluruhan, nilai parameter sesuai dengan regulasi. Metode filtrasi dengan kombinasi media silika, zeolit, dan karbon aktif efektif meningkatkan kualitas kimiawi air hujan sehingga layak untuk dikonsumsi. Namun, proses desinfeksi perlu dilakukan untuk menghilangkan mikroorganisme. Diperlukan penelitian lebih lanjut untuk mengetahui tingkat kejenuhan media filter.